Digital and Entrepreneurial Literacy in Increasing Students' Entrepreneurial Interest in the Technological Era - Purwati, Astri Ayu; Hamzah, Zulfadli; Hamzah, Muhammad Luthfi; Deli, Mazzlida Mat (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to determine the effect of digital literacy and entrepreneurial literacy on student entrepreneurial interest. The population of this study were students of private universities in Pekanbaru with a sample of 176 respondents selected through accidental sampling. The data collection method was carried out through distributing questionnaires via Google Form. The data analysis technique used is Multiple Linear Regression Analysis with SPSS. The results showed that digital literacy did not have a significant effect on student entrepreneurial interest, so the first hypothesis (H1) was rejected. Although there are indications that increasing digital literacy can increase entrepreneurial interest, the results of statistical analysis show that this influence is not strong enough to be considered significant in the context of this study. On the other hand, entrepreneurial literacy has a positive and significant influence on students' entrepreneurial interest. This means that an increase in entrepreneurial literacy can be expected to significantly increase entrepreneurial interest. Therefore, the second hypothesis (H2) is accepted. The conclusion of this study is that in the context of the population and sample studied, only entrepreneurial literacy significantly affects students' entrepreneurial interest while digital literacy does not have a strong enough or significant effect.